Pattern of Workplace Violence and Perceived Effects on Nurses’ Work Productivity in Selected Hospitals in Ibadan, Oyo State (International Journal of Studies in Nursing, 2019)
Background: Workplace violence (WPV) is a widespread occupational hazard affecting the health, safety, job attitude and productivity of the nursing workforce. This study was designed to investigate the pattern and perceived effects of WPV on nurses’ work productivity in two selected hospitals in Ibadan. Methods: This descriptive study was conducted in two purposively selected hospitals. Out of 1,418 nurses, 349 proportional sample was taken and respondents were selected using convenience sampling technique. Two validated questionnaires was used. Data were analysed using frequencies and percentages. Hypotheses were tested using chi-square at α=0.05. Results: Respondents’ age was 39 ± 6.5years; 46.8% were registered nurses, of which 48.1% had worked for 11-20 years. On pattern of violence, 49(15.6%) experienced physical violence without a weapon, 39(12.4%) experienced verbal harassment and bullying. Attackers of 33(10.5%) were patient relatives. Decreased work productivity due to WPV was reported(60, 19.1%) while no change in work productivity was reported(170,